Highly sensitive multi-layer pressure sensor with an active nanostructured layer of an organic molecular metal. Issue 1 (January 2016) - Laukhin, V; Lebedev, V; Laukhina, E; Rovira, C; Veciana, J
Abstract: This work addresses to the modern technologies that need to be instrumented with lightweight highly sensitive pressure sensors. The paper presents the development of a new plain flexible thin pressure sensor using a nanostructured layer of the highly sensitive organic piezoresistive metal β-(BEDT-TTF)2 I3 as an active component; BEDT-TTF=bis (ethylenedithio)tetrathiafulvalene. The original construction approach permits one to operate the developed sensor on the principle of electrical resistance variations when its piezoresistive layer is elongated under a pressure increase. The pressure sensing element and a set of gold electrodes were integrated into one compact multi-layer design. The construction was optimized to enable one generic design for pressure ranges from 1 to 400 bar. The pressure tests showed that the sensor is able to control a small pressure change as a well definite electrical signal. So the developed type of the sensors is very attractive as a new generation of compact, lightweight, low-cost sensors that might monitor pressure with a good level of measurement accuracy.